Aplikasi Pengumpulan Data Survei Memanfaatkan SMS Gateway - Andrew B. Osmond; Lukito Edi Nugroho; Sri Suning Kusumawardhani (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2016)
Application for collecting survey data utilizing SMS technology is used to facilitate the process of survey and data processing. Surveyor can simply send the data via SMS and the results are immediately processed in the server, then displayed via computer browser. This system is proposed because the current survey system is done manually using paper, therefore it is more risky in validity and processing. Operator must entry and process a huge amount of data, then show the result. The web-based application is build to help users operating the system easily. In addition, this application is also made generic, and can be implemented to more diverse survey. This survey data collection application is build using programming language PHP with CodeIgniter framework, javascript, and MySQL database for data storage. This application allows users to conduct surveys and data processing. The application can also minimize various problems that usually arise in manual process with a paper-based survey.